The Impact Learning Organization and Organization Culture To Employee Performance, Mediated By Knowledge Sharing (Empirical Study On Bumitama Agri LTD.) - Ade Agung Laksono (Pandawan, 2023)
The purpose of this study is to test how learning organizations affect employee performance. evaluate how company culture affects employee performance, and Test the knowledge-sharing effect of an organization. Analyze how organizational culture affects knowledge sharing. Analyze the effects of information sharing on employee performance. Test the effects of information sharing on employee performance in the organization. Analyze the effects of information sharing on company culture and employee performance. The population in this study were all staff of Bumitama Agri Ltd. who have participated in the Bumitama University Corporate Training & Development Program since 2019. This research is a survey research or it can be said as a research technique that distributes questionnaires to respondents. Data will be obtained directly from the respondents by providing questionnaires to obtain data about the learning organization, organizational culture, employee performance, and knowledge sharing. From the results of the study, it can be concluded that organizational culture has a positive effect on employee performance. A learning organization has a positive effect on employee performance. Organizational culture has a positive effect on knowledge sharing. A learning organization has a positive effect on knowledge sharing. Knowledge sharing has a positive effect on employee performance. Knowledge sharing mediates organizational culture on employee performance. Knowledge sharing mediates organizational learning on employee performance.